DIGITAL HUMAN CAPITAL STRATEGY: IMPROVING COMPANY PERFORMANCE - Arofatun, Sulis Ari; Mursid, Mansur Chadi; Isfandiar, Ali Amin; Kurniawan, Muchammad Arif; Masrur, Muhamad; Majid, Abdul; Aenurofik, Aenurofik (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Nowadays, business competition is getting tougher, and companies must be able to manage their employees well so that they can work more optimally. This research discusses the various ways companies can improve employee performance, especially in the midst of ongoing global changes. In addition, this article also discusses digital HR strategies and how technology can help companies develop better. With the rapid development of technology, companies need to adjust the way they manage HR to be more effective. Digital technology not only helps speed up administrative work, but also creates a more comfortable and productive work environment. In this research, the method used is a literature study, namely by collecting information from books, journals, articles, and other relevant sources. From the results of the research, it is evident that the application of technology in HR management has a major impact on company performance. With a digital system, work becomes more efficient, the employee recruitment process can be faster, and employee engagement and satisfaction also increase. But of course, there are challenges to be faced, such as employees who are difficult to accept change or lack of skills in using technology. Therefore, it is important for companies to really understand how a digital HR strategy can be implemented properly. If done the right way, companies can be more competitive and successful in the long run by utilizing technology to manage HR more efficiently. Keywords: Digital HR strategy, Company performance, Technology, Human resource management, Synergy